Pretreatment and bioprocess trials in various reactor system on lignocellulosic biomass for cellulosic biomaterials / Amizon Azizan … [et al.] - Azizan, Amizon; Aida Jusri, Nur Amira; Azmi, Intan Suhada; Abu Darim, Rosmaria; Mohd Salleh, Ruzitah; Ibrahim, Norliza; Abd Rahman, Mohd Faizal; Salihon, Jailani (Universiti Teknologi MARA, 2021)
Pre-treatment on lignocellulosic biomass prior to extraction of biomaterials, degradation of bioproduct, or production of biomaterial/bioproduct/biofuel, crucially influences the intended outcomes. The pre-treatment of oil palm fronds (OPF), one of the most abundant agriculture residues in Malaysia, can be conducted based on the need of the methodology, either for small, lab, pilot, or industrial scales. In this article, examples of reactors for the pre-treatment for instance microreactor (Bioshake iQ), conical shake flask, and mini-cylindrical reactor scale (fabricated) as well as the monitoring bioreactor (BlueSens Monitoring GmbH) reactor system dedicated for fermentation process using the outcome material from pre-treatment process, are presented. All pre-treatment trials with ionic liquid (IL) of 1-ethyl-3- methylimidazolium acetate [EMIM]Ac on OPF were conducted with a scaling-up strategy from micro-to-macro to fabricated reactors, monitoring Crystallinity Index (CrI) and Lateral Order Index (LOI). Electron beam irradiation pretreatment using 1000kGy was also tested in macroscale mode for CrI and LOI. Effectiveness of approximately 23 to 37% of CrI via microreactor experiments using 50, 70, and 90% v/v of [EMIM]Ac and at a temperature of 99o C was observed. Higher concentration of IL and temperature with nearly insignificance of solid loading of OPF in reaction liquid to the increase of the amorphous level of OPF was reported by macroscale mode in the 570-mL fabricated reactor. A short oxygen uptake rate (OUR) phase was observed in a 500-mL BlueSens shake flask with the real-time monitoring systems for 45-mL working volume, a nearly 10% of the total reactor volume for saccharification-fermentation using Escherichia coli K011 ATCC 55124 on approximately 2.22% w/v pre-treated OPF from macroscale mode. Various data examples from these micro-to-macro scales including in a fabricated reactor system mode are crucially needed for further observations prior to pilot or industrial scales, needing a systematic data collection to be simulated and investigated in the future.